Analisis Konstruksi Kapal Nelayan Tradisional di Kabupaten Bengkalis Provinsi Riau - Nasution, Polaris; Hutauruk, Ronald Mangasi (Jurnal Perikanan dan Kelautan, 2016)
Difficulties to obtain good wooden materials as vessels primary materials conduce to drop the quality and the lifetime of a ship. To satisfy new ship building demand, a shipyard tends to apply fast building and ignores the ship quality, types, and dimension and materials characteristics. Shipyard also did not consider about the technical and operational aspects as rule and regulations for wooden vessels. Un-optimal ship construction make it low in quality and at the end, it cannot be used directly after handover. In general, the cause of damage of ship was due to unsatisfying of construction criteria such as the types of wood, including the age and the length of the wood used for its construction. In addition, it had been found that there were unsatisfied ships operating under construction regulation.